2019
DOI: 10.18172/cig.3616
|View full text |Cite
|
Sign up to set email alerts
|

Clearing shrubland as a strategy to encourage extensive livestock farming in the Mediterranean mountains

Abstract: The European Mediterranean highlands have undergone a sharp economic decline from the mid-20 th century, causing heavy environmental impacts and loss of ecosystem services. These mountain areas have limited opportunities to integrate into in the current financial system, which demands high productivity from workers and a very competitive product. Extensive livestock farming is one of the few activities able to survive in this context, as it needs little labour and can make use of poor grazing resources. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 50 publications
0
21
0
12
Order By: Relevance
“…Pastoralism was also less intensively subsidized in peri-urban areas, with poor (or no) incentives at community scale. In this context, an intense decline in livestock farms was associated with (i) more severe wildfires, (ii) a higher incidence of fires burning woodlands, and (iii) ra higher spatial heterogeneity of fire events, being motivated by multiple causes that include a lack of subsidies for livestock, conversion of forest and non-forest natural areas to urban settlements, poor forest management, and land abandonment [19,75,92].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pastoralism was also less intensively subsidized in peri-urban areas, with poor (or no) incentives at community scale. In this context, an intense decline in livestock farms was associated with (i) more severe wildfires, (ii) a higher incidence of fires burning woodlands, and (iii) ra higher spatial heterogeneity of fire events, being motivated by multiple causes that include a lack of subsidies for livestock, conversion of forest and non-forest natural areas to urban settlements, poor forest management, and land abandonment [19,75,92].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of pastoralism and the increasing spatial heterogeneity of wildfires were demonstrated to be associated with (rapid) changes in land-use, lack of subsidy for livestock activities and peri-urban agriculture, simplified (or no) forest management, and competitive urban land-use impacting fragile natural contexts [19,75,92]. Additional efforts aimed at (i) exploring fuel management for wildfire prevention in peri-urban districts and (ii) assessing efficiency of (pre-and post-)fire fuel management using advanced methodologies should be developed [34,44,48,[93][94][95][96].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that the livestock sector is closely linked to forest fires, as a large part of these start with the use of fire as a tool in regenerating pastures. Also, Lasanta et al (2019) found that, in the Leza Valley (north-western Iberian System), shrubland clearing led to an increase in livestock numbers, rising from 1,833.9 LU in 1972 to 7,207.8 LU in 2017, with the size of farms also expanding (27.6 LU in 1972to 115.2 LU in 2017. In addition, new livestock farms are being started by people from outside the study area (41.7% in 2017), which is a clear factor in socio-economic and environmental sustainability.…”
Section: Combining Extensive Livestock Grazing With Prescribed Fires mentioning
confidence: 99%
“…deterioro por incendio catastrófico, dando lugar a la expansión de matorrales que impiden o dificultan el pastoreo de noviembre a marzo. El reto más importante de cara al futuro es decidir cómo se gestiona este paisaje abandonado y recolonizado por bosques y matorrales, aspecto en el que hay todavía mucha controversia (Conti & Fagarazzi, 2004;Cramer et al, 2007;Navarro & Pereira, 2012;Nogués et al, 2016;Lasanta et al, 2015Lasanta et al, , 2018Robledano Aymerich et al, 2016). El asunto es de gran transcendencia no solo porque afecta a la conservación de paisajes con gran valor cultural; también afecta a cuestiones tales como la biodiversidad (Lasanta Martínez et al, 2013b), el funcionamiento hidrológico de laderas y la generación de escorrentía (Beguería et al, 2003;Lana-Renault et al, 2018).…”
Section: Los Cambios Recientes Y Sus Impactos: La Deconstrucción De Uunclassified